Pengembangan media pembelajaran interaktif berbantuan Microsoft PowerPoint pada materi ciri-ciri dan pertumbuhan makhluk hidup untuk siswa sekolah dasar (Master of Elementary Education, University of Riau, 2022)
This research has two objectives, namely, to develop learning media based on interactive microsoft power point for characteristics and growth of living things, and to determine whether learning media is appropriate to use interactively as a medium in learning characteristics and growth of living things in third grade of elementary school. The study used ADDIE development model consisting of 5 stages starting from analysis, design, development, implementation, and evaluation The participants for the impelemtation of the media was five third grade students from a public elementary school in Pekanbaru, Riau, Indonesia. The findings indicated that the level of feasibility of learning media using interactive microsoft power point was declared feasible based on the self evaluation by the researchers and students’ opinion. Students were interested and able to understand the material presented through an interactive display that was designed. Learning media using interactive power point has been carried out in a trial phase in increasing student motivation and enthusiasm for learning. Therefore, the interactive power point learning media developed is feasible in supporting student learning of characteristics and growth of living things and is effective in increasing student learning concentration and motivation.